Antibacterial Activity of Leaves and Rhizome of Curcuma xanthorrhiza Essential Oils on Different Distillation Time - Nur Syafiqah Nadiah Mohammad Rafi; Irmanida Batubara; Anthony Nyangson Steven (Tropical Biopharmaca Research Center, IPB University, 2018)
This research aims to determine the antibacterial activity of Curcuma xanthorrhiza leaves and rhizomes essential oil with different distillation time of 2 hours, 4 hours and 6 hours against Escherichia coli and Staphylococcus aureus. The essential oils produced then separated by thin layer chromatography (TLC) with n-hexane: toluene: dichloromethane 1:8:1 as the mobile phase. The result shows that on the first two hours distillation gave the highest yield compared to the next two hours or four hours. Based on TLC chromatograms, the highest content of compounds found at 4-6 hours distillation time. TLC bioautography contact was used for antibacterial activity tested on chromatogram and the clear zone appears on it indicates the spots were active as antibacterial activity against both bacteria with Rf values of 0.35 and 0.49 for rhizomes, rhizome essential oils 4-6 hours distillation time as the most significance active.